Toxicity and Lethality Evaluations of Koordersiodendron pinnatum Leaves Methanolic Extract in DDY Mice - Banjarnahor, Sofna Dewita Sari; Dewijanti, Indah Dwiatmi; Angelina, Marissa; Fajriah, Sofa (Journal of Tropical Life Science, 2016)
The study of toxic features of Koordersiodendron pinnatum is vital for further studies of its pharmacological activities. Acute toxicity test was done on methanolic extracts of K. pinnatum in DDY mice. Animals were grouped into five: Group 1 was given 1 mL solution of 2.5% Tween 80 in a single oral dose; the remaining groups were orally given a single dose of 2, 4, 8 and 16 g/kg of K. pinnatum, respectively. Toxic effects of the extract were evaluated on the basis of behavioral observations in the form of locomotor activity; curiosity; defecation; urination and also animal mortality. Observations were carried out for 14 days. No significant changes on body weight, and behavioural activities were recorded. Mortality was recorded up to 2% of the male group, and no mortality within the female group. The extract is practically non toxic for both male and female (LD50>15 g/kg).